The Arthroscopic Intra-Articular Stabilization of the Shoulder for Irreparable Rotator Cuff Tear: A New Technique Proposal - Luciani, Pierfrancesco; Farinelli, Luca; De Berardinis, Luca; Gigante, Antonio (Frontiers in Surgery, 2021)
Background: Superior Capsular Reconstruction (SCR) has shown good results in the management of irreparable rotator cuff tears due to the depressive effect on the humeral head, but it is a technically demanding and expensive procedure. Purpose: We hypothesized that an intra-articular neoligament that prevents the superior translation of the humeral head could give similar results in terms of superior translation of humerus (STH) and range of motion (ROM). Study design: To compare our proposed technique and the SCR we conducted a biomechanical study on ten porcine shoulders in a custom shoulder testing system. Methods: STH and total rotational ROM were quantified in the following 4 scenario: (1) when the rotator cuff was intact, (2) after cutting the supraspinatus tendon, (3) after the reconstruction of the superior capsule by long head of the biceps tendon (LHB) (4) after an arthroscopic intrarticular stabilization by an intrarticular graft. Our proposed technique provides the creation of a humeral and glenoid tunnel, the passage of a graft through these tunnels under arthroscopic guidance, and the graft fixation in the two tunnels. We analyzed the STH and total ROM in each scenario. Results: Regarding the STH, we reported that the present proposed technique is characterized by a significant reduction of superior translation at 0° and 45° compared to scenario 2. In addition, the comparison between our proposed technique and SCR showed a significant difference of STH at 0 ° of abduction. Total rotational ROMs of the two tenchinques were similar to scenario 2. Therefore, the use of an intra-articular ligament that prevents the STH can restore shoulder stability in irreparable rotator cuff injuries at both 0 ° and 45 ° of glenohumeral abduction without apparently limiting the total rotational ROM. Conclusion: Our proposed technique could be an important treatment option in irreparable rotator cuff tears, especially in patients under 65 in whom reverse shoulder arthroplasty (RSA) has shown poor results and many complications.